Colonoscopy may be weak link in organised colorectal cancer screening programme with faecal immunochemical test. (June 2022) - Denis, Bernard; Gendre, Isabelle
Objective: To evaluate the quality of colonoscopies performed after a positive faecal immunochemical test in the French colorectal cancer screening programme. Methods: Retrospective analysis of all colonoscopies performed between 2015 and 2019 after a positive quantitative faecal immunochemical test in the population-based colorectal cancer screening programme organised in Alsace, part of the French programme. The following indicators were evaluated: annual colonoscopy volume, caecal intubation rate, adenoma detection rate, proximal serrated lesion detection rate and proportion of patients referred directly to surgery for benign polyp management. Endoscopists who performed <30 faecal immunochemical test positive colonoscopies were non-assessable. Results: Overall, 13, 455 faecal immunochemical test-positive colonoscopies performed by 116 community gastroenterologists were included, 13, 067 of them by 80 assessable endoscopists. The overall caecal intubation, adenoma detection and proximal serrated lesion detection rates were 97.9%, 57.6% and 7.6%, respectively. They were <90%, <45% and <1% for 1.3%, 12.5% and 6.3% of the endoscopists, respectively. Overall, 1028 (7.9%) individuals were examined by 13 low-performing endoscopists and 328 (2.4%) individuals by 33 low-volume non-assessable endoscopists. Among 9133 individuals harbouring polyps, 155 (1.7%) had unwarranted surgery for a benign polyp. Overall, 1487 individuals (11.1%; 95% confidence interval 10.5–11.6) were not given the best possible chances, whereas 5545 individuals (41.2%; 95% confidence interval 40.4–42.0) were offered the best possible chances by 37 endoscopists. Conclusions: At programme level, the key performance indicators evaluated largely exceeded the target standards. At individual level, at least one in nine individuals was not given the best possible chances during faecal immunochemical test-positive colonoscopies by a minority of poor-performing and/or low-volume endoscopists.